2021
DOI: 10.1016/j.jse.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Sprengel's deformity: an analysis of surgically and nonsurgically treated patients

Abstract: Background: Sprengel's deformity is a congenital anomaly of the scapula and can be associated with reduced shoulder mobility and esthetic concerns. Controversies remain regarding its natural history, radiographic findings, and optimal treatment strategy. Methods: A total of 74 Sprengel's shoulders in 71 patients presenting to a pediatric referral hospital were retrospectively reviewed including 24 surgically treated shoulders. Median age at initial presentation was 3.8 years. Median age at the final follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-seven patients (22%) were grade 4, 283 patients (64.2%) were grade 3, 51 patients (11.5%) were grade 2 and 10 patients (2.3%) were grade 1. Fifteen studies (283 patients) used Rigault’s classification [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 , 58 , 60 ]: 41% reported score 3 (116/283), 59% score 2 (167/283), whereas no patient had score 1 at the preoperative assessment. Only two papers did not report any vertebral-shoulder connection in their patients [ 9 , 40 ]; the other studies identified a connection between the scapula and spine in 305 patients (46.9%), represented by an omovertebral bone bar (264 patients), fibrous bridge (22 cases) or cartilaginous bar (19 cases).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations